(untitled) (AYUSHDHARA, 2018)
Ayurveda is an age old system of medicine that was penned by Acharyas who were considered to be epitomes of knowledge. The language of the text is Sanskrit and the meanings are obtained by reading the commentary that is given below. The classical texts also propose certain tools that can be used to code and decode the concepts mentioned in the text. Tantrayukti and Vadamarga are two such tools explained in classical a text that has to be used by an intelligent/mediocre student or physician to understand the concepts and apply it in the most appropriate way. Tantrayukti is a tool proposed for interpretation where as Vadamarga deals with the protocols to be followed in debates. The subject knowledge becomes complete only when the proper application of Tantrayukti and Vadamarga is also known. Though Tantrayukti is mentioned in Ashtanga Sangraha and Hridaya, Charaka Samhita and Sushruta Samhita, only Charaka exclusively explains about Vadamarga. So in this article an attempt is made to compare the similarities and dissimilarities of Vadamarga and Tantrayukti.